2005
DOI: 10.1158/1078-0432.ccr-1004-0001
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pharmacokinetics of Various Monoclonal Antibodies Labeled with a New Trifunctional Chelating Reagent for Simultaneous Conjugation with 1,4,7,10-Tetraazacyclododecane-N,N′,N″,N‴-Tetraacetic Acid and Biotin before Radiolabeling

Abstract: Purpose: Knowledge of the blood pharmacokinetics of monoclonal antibodies is crucial in deciding the optimal time for starting the administration of a “clearing agent” or using a “clearing device.” The primary purpose was to investigate whether the pharmacokinetics of various antibodies labeled with the same chelator and 111In differed significantly after i.v. injection in immunocompetent rats. A new trifunctional chelator called “1033” containing a biotin and a radiometal chelation moiety is introduced, makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…In addition, we presented a novel method for a quantitative correlation between the reduction of the peripheral white blood cell and platelet concentrations as a function of the absorbed dose to the red marrow. When reviewing the raw data from the previously described kinetic study by Wang et al, 15 the RMBLR was shown to increase with time post injection (Fig. 1).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In addition, we presented a novel method for a quantitative correlation between the reduction of the peripheral white blood cell and platelet concentrations as a function of the absorbed dose to the red marrow. When reviewing the raw data from the previously described kinetic study by Wang et al, 15 the RMBLR was shown to increase with time post injection (Fig. 1).…”
Section: Discussionmentioning
confidence: 87%
“…The dosimetry calculations were based on recently published kinetic data extracted from dissected animals and blood samples using 111 In-labeled 1033-BR-96 antibodies. 15 Tissue samples from muscle, kidney, liver, spleen, bowel, lymph nodes, lung, bone marrow, tumor, ventricle, and pancreas were collected from three animals at each time point-1.5, 8, 24, 48, and 96 h post injection-and measured in a well-type gamma counter (LKB, Finland) to calculate the percentage of injected activity per gram (%IA/g). Imaging from a planar scintillation camera (General Electric Maxi Camera 535, Milwaukee, WI) was performed prior to dissection to determine total body activity and used for determination of the activity in the remainder.…”
Section: Iic Biokinetic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…If the data of the patients could be described by common kinetic parameters this would possibly allow using a simplified method for dosimetry in radionuclide therapy. 4,5 The smaller the differences among the patients, the better the fit will be with shared parameters. For the model consisting of two exponential functions ͑four parameters͒ all 16 combinations of shared or nonshared parameters were investigated, i.e., 16 different models were examined.…”
Section: Iic5 Equality Of Biokineticsmentioning
confidence: 99%
“…This may be of interest, for example, in radionuclide therapy, because equal kinetic parameters would possibly allow using a simplified method for dosimetry. 4,5 Different criteria exist to choose the best model ͓e.g., F-test, 6 Imbimbos I P proposed in the pharmacokinetic context, 7 the AIC, 8 and the Bayesian information criterion 9 ͑BIC͔͒. In the following investigation we concentrate on the commonly used F-test and the corrected Akaike information criterion ͑AICc͒, which is a modification of the AIC recommended for small sample sizes in comparison to the number of model parameters.…”
Section: Introductionmentioning
confidence: 99%